Analisis Dampak Broken Home terhadap Minat Belajar Siswa di SDN Pasirkamuning I Karawang - Bachruddin, Rizal; W, Undang Ruslan (Lembaga Yasin AlSys, 2022)
This research is motivated by the problem of a broken home that affects children's interest in learning at school. This study is intended to examine the effect of broken homes on students' interest in learning at SDN Pasirkamuning I Karawang. The method in this research is descriptive in the form of qualitative research. The data sources in this study were students from broken home families. Data collection techniques in this study were carried out through interviews, observation and documentation. The analysis in this study is presented in a qualitative descriptive manner using three informants. The results of this study indicate that students who come from broken home families have academic and behavioral problems and some do not experience them. Students' interest in learning from families is cut off. There are students who have an interest in learning, and students who do not have an interest in learning because they have a family background. The conclusion of this study is that students who come from damaged families are assessed positively and negatively from damaged homes. Students' interest in learning from families is divided, some are interested in learning and some are not interested in learning.